Degradation Dynamics and Conservation Imperatives of Phewa Wetland, Nepal - Pokharel, Ramjee Prasad; Subedi, Daya Sagar (The Himalayan Geographers, 2024)
Phewa Wetland, a vital ecological area within Nepal’s Phewa Lacustrine Plain, is experiencing rapid degradation due to escalating natural and anthropogenic pressures. This study employs a mixed-method approach combining field observation, GIS-based spatial analysis, and secondary data review to assess the wetland’s ecological status, sedimentation trends, biodiversity, and human impacts. Between 1978 and 2024, the wetland area is unstable in size. Urban expansion, agricultural encroachment, invasive plants and sediment inflow is major contributors. Additional threats include nutrient overloading, unregulated waste disposal, and weak policy enforcement. The findings underscore the urgent need for integrated conservation strategies such as legal boundary demarcation, agrochemical regulation, sediment control infrastructure, invasive species management, and active community involvement. Without immediate intervention, Phewa Wetland faces the risk of ecological collapse, endangering both biodiversity and the livelihoods that depend on it. Preserving this wetland is essential not only for local sustainability but also for Nepal’s broader environmental resilience.